2022
DOI: 10.1177/10776990221105588
|View full text |Cite
|
Sign up to set email alerts
|

After the Killing of Atatiana Jefferson: Black Stakeholder Experiences Within a Municipal Listening Structure

Abstract: Starting with a public relations pioneer’s maxim to “listen to stakeholders,” many contemporary scholars have emphasized listening as the key to the inclusion of marginalized communities. Based on 25 in-depth interviews including 19 Black residents of Fort Worth, this study amplifies the voices of Black community members after the killing of Atatiana Jefferson in her home by a White police officer. Their perceptions of systemic racism within the city’s listening processes and their recognition of pseudo-listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Policy must be more than what is merely written, it must be consistently enforced. Research specific to FWPD police use of force violations has found this has not been the case (del Carmen et al., 2022; O'Neil, English & Lambiase, 2022). Like other scholars before us, we find that policing is entrenched in historical racial bias and carries the burden of a legacy of white supremacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy must be more than what is merely written, it must be consistently enforced. Research specific to FWPD police use of force violations has found this has not been the case (del Carmen et al., 2022; O'Neil, English & Lambiase, 2022). Like other scholars before us, we find that policing is entrenched in historical racial bias and carries the burden of a legacy of white supremacy.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary reports from police reform specialists showed a trend of unlawful use of force tactics condoned by the command personnel in over 200 FWPD cases (Allen, 2022; del Carmen et al., 2022). Over a decade of review from similar police reform specialists and scholars has led to the conclusion that cultural change is needed for the FWPD in regards to officer conduct among citizens of colour (del Carmen et al., 2022; O'Neil, English & Lambiase, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…These stakeholders have their own goals that could affect the sustainability of the organization because they frequently hold power and legitimacy (Mitchell et al , 1997). Hence, stakeholder groups who directly or indirectly control resources may need to be notified about important issues (O’Neil et al , 2022a) such as corporate intents on economic, social and environmental issues. The mission, vision and value statements communicate what matters to the organization on sustainability to different stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%